Communication Model for Promoting Historical Tourism in Kupang City - Ferly Tanggu Hana; Monika Wutun; Silvania Stella Epiphania Mandaru; I Gusti Ayu Rina Pietriani; Abner Paulus Raya Sanga (CV. AFDIFAL MAJU BERKAH, 2023)
The expansion of transportation, communication, and infrastructure has accelerated the development of the tourism sector in Kupang City in recent years. However, not all sorts of tourism are successfully established, and historical tourism in Kupang City is one of them. This is ironic because, while technology has not yet made historical tourism a viable alternative for travelers, today's promotion should be simple and inexpensive. Even though the potential for tourist visits in Kupang City is fairly large, historical tourism promotion is the subject of this study due to a lack of advertising on this sort of tourist item. Therefore, the objectives of this research are to identify promotional activities and develop a communication model for promoting historic tourism in Kupang City. The case study technique was employed in this research, and the target informants were Penta Helix stakeholders in the tourism sector, they are the government, business people, communities, academics, and media. This study found that promotional activities at numerous historical tourism sites are still poorly managed. Furthermore, the underdevelopment of historical tourism is primarily due to a lack of political will on the part of leaders, the public's lack of historical information literacy, and a lack of mass media coverage, including ineffective use of social media. The model established in this study is a promotion communication model that includes the role of all stakeholders with a focus on historical tourist assets, messages, and media.